2020
DOI: 10.1155/2020/5781913
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Mass Index and Short‐Term Clinical Outcomes in Critically Ill Patients with Sepsis: A Real‐World Study

Abstract: Background. Obesity is now recognized as one of the major public health threats, especially for patients with a critical illness. However, studies regarding whether and how body mass index (BMI) affects clinical outcomes in patients with sepsis are still scarce and controversial. The aim of our study was to determine the effect of BMI on critically ill patients with sepsis. Materials and Methods. We performed this study using data from the Medical Information Center for Intensive Care III database. A multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Recently, the NUTRIC and APACHE scores have been reported as good scoring systems that reflect the severity of illness affecting the patients' metabolism, which finally results in malnutrition. Additionally, some studies have shown the association of low BMI with unfavorable outcomes in critically ill patients [23]. In contrast, previous studies presented that the patients with higher BMI showed better outcome in ICU care, which is called "Obesity Paradox" [24e27].…”
Section: Tools For Nutritional Risk Stratificationmentioning
confidence: 99%
“…Recently, the NUTRIC and APACHE scores have been reported as good scoring systems that reflect the severity of illness affecting the patients' metabolism, which finally results in malnutrition. Additionally, some studies have shown the association of low BMI with unfavorable outcomes in critically ill patients [23]. In contrast, previous studies presented that the patients with higher BMI showed better outcome in ICU care, which is called "Obesity Paradox" [24e27].…”
Section: Tools For Nutritional Risk Stratificationmentioning
confidence: 99%
“…A total of 3865 records were identified via a systematic search of databases published before March 28, 2023, and screened for inclusion based on eligibility criteria. After reviewing the titles and abstracts, 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] were selected for inclusion in this study. Specifically, these studies reported on the association between obesity and sepsis prognosis, with 8 [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , 23 ] of them focusing on overweight patients and 6 [ 14 , 16 , 18 , 20 , 21 , 35 ] of them restricting the analysis to patients with low weight.…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis comprised 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] encompassing data from multiple countries or regions with a total of 521,207 individuals, and two of which were prospective cohort studies. The follow-up time varied across the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were extracted using structured query language (SQL), the website and code to generate support for MIMIC-III documentation are released publicly. [22][23][24]…”
Section: Patient Datamentioning
confidence: 99%